Land Surface Coverage, Main Vegetation and Physical Soil Characteristics of West Side of Lawu Mountain - Rahayu Rahayu; Puguh Karyanto (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
Sustainability of catchment area management of a mountain requeres identification the vegetation and condition of the major vegetation. This reserachs purpouse was characterizing major vegetation, coverage and soil properties at 1000 m elevation sea level to the top of Lawu mountain. Survey was started by identification of every vegetation unit followed by taking soil sample that was analyzed in laboratory for identifying the properties. Sampling and identification conducted close by common climbing track line to the top, including Jogorogo and Cemoro Sewu East Java, and Cemoro Kandang and Sukuh Central java. Coverage of vegetation used sattellite immage landsad and was analyzed by Arview software. Results showed that intens and dense forest was 36,22% and the other was rare density forest. Major vegetation of Lawu mountain was Pinus (Pinus merkusii), Cemara (Casuarina equisatifolia), Tanganan (Schleptera sp), Akasia gunung (Acasia decurren), rumput vestuca, Cantigi (Vaccinium sp) kayu pasang (Lithocarpus pruinusa) and vegetables on agriculture land. Every type of vegetation unit had different soil physycal properties of topsoil, while elevation had effect on soil bulk volume and porocity.